KEJAHATAN SIBER DAN PERDAGANGAN DATA GELAP (DARK WEB): TANTANGAN HUKUM INDONESIA DALAM KONTEKS BUDAPEST CONVENTION - Moeso Novianto; Nur Arfiani (Bajang Institute, 2025)
The rapid growth of digital technology has led to cybercrimes such as illegal data trade on the Dark Web, which are anonymous and transnational, posing serious threats to national data security. This study aims to analyze the roles of the Electronic Information and Transactions Law (ITE Law) and the Personal Data Protection Law (PDP Law) in addressing such crimes, as well as to examine the relevance of the Budapest Convention for Indonesia. Using a normative juridical method with statutory and conceptual approaches, the study finds that weak national legal implementation and the absence of Budapest Convention ratification hinder law enforcement, making stronger international cooperation urgently necessary.